Peran Pola Asuh Orang Tua Dalam Membentuk Konsep Diri Pada Anak - Afida Vona; Koryna Aviory (Jurnal Psikologi TALENTA, 2020)
The purpose of this article is to describe the role of parents in parenting to shape the child's self-concept. The method applied is literature study or commonly known as literature study. This paper is derived from the ideas or views of journal authors and books in accordance with the discussion. Data analysis is the reading sources are compiled, analyzed, then the final result is concluded. The results of this study explain that parenting parents really need to be learned let alone understood by parents wherever they are, because it greatly influences the form of the child's self-concept. Positive education, as directed, is given understanding, advised so that children can correct their mistakes, allowing the growth of positive self-concepts in children For example the child is able to adjust quickly, confidently, willing to try and dare to make decisions. This is known as democratic parenting. But on the contrary, bad education from parents, such as often scolding when children make mistakes or fail (applying authoritarian parenting) allows the embedded negative self-concept in children. Negative self-concept is synonymous with self-doubt, fear of determining decisions, and minimal adaptability.